The Notary Role of Binding Guarantee on Land Rights in Credit Take Over Between Different Banks - Suyitno Suyitno; Nizar Anwar; Gunarto Gunarto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
This study aims to: 1) to analyze the role of the notary on the binding guarantees the right to land in the credit of take over between different banks. 2) to analize the mechanismof binding process guarantees the right to land in the credit take over between different banks. The data used in this study are primary data, secondary data and data tertiary to support the process of this research, which was then analyzed by descriptive analysis method.Based on the results of data analysis can be concluded that: 1) relating the fine refinance loan, then the role of the Notary / PPAT should be promoting the principle of